Peran Lingkungan Kerja, Kepemimpinan, Dan Kompensasi Dalam Menurunkan Turnover Intention - Muh.Sabri; Halim, Agus (CV. SINAR HOWUHOWU, 2026)
Turnover intention describes an employee's desire or intent to resign from an organization or change jobs, serving as a critical indicator of human resource stability within a company. High turnover intention can lead to increased recruitment costs, decreased productivity, and disruptions in the organization's operational continuity. Based on various empirical studies, factors such as the work environment, leadership, and compensation play a significant role in influencing employee turnover intention. A conducive work environment characterized by adequate facilities, positive relationships among colleagues, and a safe psychological climate can enhance employee engagement and reduce the intent to leave the organization, thereby creating a sense of comfort and higher job loyalty. Effective leadership, particularly transformational or supportive leadership styles, can increase motivation, commitment, and job satisfaction through clear communication, emotional support, and fair decision-making, which ultimately reduces turnover intention. Furthermore, fair and competitive compensation including salary, benefits, bonuses, and other non-financial rewards is proven to be negatively correlated with turnover intention; the more optimal the compensation system perceived by employees, the lower their intention to move elsewhere. Recent quantitative research shows that the simultaneous application of these three variables a positive work environment, supportive leadership, and appropriate compensation can significantly decrease turnover intention rates across various organizational contexts. This aligns with findings that improving the quality of these three factors results in a decline in the number of employees aspiring to leave the organization and strengthens overall employee retention.